Resilient Oracle PL/SQL building resilient database solutions for continuous operation - Morris, Stephen B. (O'Reilly Media, 2023)
As legacy and other critical systems continue to migrate online, the need for continuous operation is imperative. Code has to handle data issues as well as hard external problems today, including outages of networks, storage systems, power, and ancillary systems. This practical guide provides system administrators, DevSecOps engineers, and cloud architects with a concise yet comprehensive overview on how to use PL/SQL to develop resilient database solutions. Integration specialist Stephen B Morris helps you understand the language, build a PL/SQL toolkit, and collect a suite of reusable components and patterns. You'll dive into the benefits of synthesizing the toolkit with a requirements-driven, feature-oriented approach and learn how to produce resilient solutions by synthesizing the PL/SQL toolkit in conjunction with a scale of resilience. Build solid PL/SQL solutions while avoiding common PL/SQL antipatterns Learn why embedding complex business logic in SQL is often a brittle proposition Learn how to recognize and improve weak PL/SQL code Verify PL/SQL code by running data-driven, in-database tests Understand the safe operation, maintenance, and modification of complex PL/SQL systems Learn the benefits of thinking about features rather than just use cases Define good requirements for PL/SQL and hybrid solutions involving PL/SQL and high level languages.
Includes index. - Description based on online resource; title from digital title page (viewed on August 11, 2023)
Keywords: Oracle (Computer file); PL/SQL (Computer program language); Relational databases; PL/SQL (Langage de programmation); Bases de données relationnelles